Sosialisasi Menggunakan Media Permainan Tradisonal Engklek Untuk Mengenal Bangun Datar di SDN 27 Lubuk Alung - Deby Erdriani; Dewi Devita; Laila Marhayati (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aimed to evaluate the effectiveness of using traditional Engklek games for socialization to introduce plane figures at SDN 27 Lubuk Alung. The socialization activities were successfully conducted, achieving the following indicators: 1) Participant Engagement: The target number of participants was met with high levels of engagement. Observations during the activities revealed that students were very active in answering the questions incorporated in the Engklek game. They displayed enthusiasm by eagerly raising their hands upon completing the tasks. 2) Achievement of Objectives: After the series of socialization activities, a feedback session was conducted with the students. The results indicated that students felt happy and more motivated to learn through this method. These findings suggest that incorporating traditional games like Engklek into educational activities can enhance student engagement and motivation, thereby facilitating effective learning.